A Systematic Review of Vaccination Guidance for Humanitarian Responses - Lauren E. Allison; Mervat Alhaffar; Francesco Checchi; Nada Abdelmagid; Barni Nor; Majdi M. Sabahelzain; Page M. Light; Neha S. Singh (Vaccines, 2023)
Delivering vaccines in humanitarian response requires rigourous and continuous analysis of evidence. This systematic review mapped the normative landscape of vaccination guidance on vaccine-preventable diseases in crisis-affected settings. Guidance published between 2000 and 2022 was searched for, in English and French, on websites of humanitarian actors, Google, and Bing. Peer-reviewed database searches were performed in Global Health and Embase. Reference lists of all included documents were screened. We disseminated an online survey to professionals working in vaccination delivery in humanitarian contexts. There was a total of 48 eligible guidance documents, including technical guidance (n = 17), descriptive guidance (n = 16), operational guidance (n = 11), evidence reviews (n = 3), and ethical guidance (n = 1). Most were World Health Organization documents (n = 21) targeting children under 5 years of age. Critical appraisal revealed insufficient inclusion of affected populations and limited rigour in guideline development. We found limited information on vaccines including, yellow fever, cholera, meningococcal, hepatitis A, and varicella, as well as human papilloma virus (HPV). There is a plethora of vaccination guidance for vaccine-preventable diseases in humanitarian contexts. However, gaps remain in the critical and systematic inclusion of evidence, inclusion of the concept of “zero-dose” children and affected populations, ethical guidance, and specific recommendations for HPV and non-universally recommended vaccines, which must be addressed.